2015
DOI: 10.1073/pnas.1414593112
|View full text |Cite
|
Sign up to set email alerts
|

Endo-β- N -acetylglucosaminidase forms N -GlcNAc protein aggregates during ER-associated degradation in Ngly1-defective cells

Abstract: The cytoplasmic peptide:N-glycanase (PNGase; Ngly1 in mice) is a deglycosylating enzyme involved in the endoplasmic reticulum (ER)-associated degradation (ERAD) process. The precise role of Ngly1 in the ERAD process, however, remains unclear in mammals. The findings reported herein, using mouse embryonic fibroblast (MEF) cells, that the ablation of Ngly1 causes dysregulation of the ERAD process. Interestingly, not only delayed degradation but also the deglycosylation of a misfolded glycoprotein was observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
117
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 46 publications
(51 reference statements)
3
117
1
Order By: Relevance
“…These results clearly show that the POSs were mainly monophosphorylated, consistent with the predictions made by previous biochemical studies (10,11,14). Man␣1,2Man␣1,3(Man␣1,6)Man␤1, 4GlcNAc␤1,4GlcNAc-P-Because ENGase catalyzes the hydrolysis of ␤1,4-linkage of the N,NЈ-diacetylchitobiose core of protein-bound (24) and unbound (19,21) forms of high mannosetype glycans in the cytosol of mammalian cells, we speculated that POSs, which are exclusively localized in the cytosol (10, 13, 14), may also serve as physiological substrates for ENGase. To test this hypothesis, the amounts and glycan structures of the POSs were compared between wild-type and Engase Ϫ/Ϫ MEFs.…”
Section: Resultssupporting
confidence: 92%
“…These results clearly show that the POSs were mainly monophosphorylated, consistent with the predictions made by previous biochemical studies (10,11,14). Man␣1,2Man␣1,3(Man␣1,6)Man␤1, 4GlcNAc␤1,4GlcNAc-P-Because ENGase catalyzes the hydrolysis of ␤1,4-linkage of the N,NЈ-diacetylchitobiose core of protein-bound (24) and unbound (19,21) forms of high mannosetype glycans in the cytosol of mammalian cells, we speculated that POSs, which are exclusively localized in the cytosol (10, 13, 14), may also serve as physiological substrates for ENGase. To test this hypothesis, the amounts and glycan structures of the POSs were compared between wild-type and Engase Ϫ/Ϫ MEFs.…”
Section: Resultssupporting
confidence: 92%
“…As shown in Fig 1D, the loss of Ngly1 in MEF cells from Ngly1 −/− mice was confirmed. In the case of ENGase, we confirmed the loss of the ENGase activity through an activity assay in a previous study [27] as well as by conducting a detailed structural analysis of the free oligosaccharides (fOSs) in the cytoplasm of MEF cells [28]. The Ngly1 heterozygous ( Ngly1 −/+ ) mice were fertile and did not show any obviously recognizable phenotypes.…”
Section: Resultssupporting
confidence: 79%
“…To this end, we used mice (C57BL/6 background mice) that had been generated in a previous study, in which the Ngly1 and Engase genes had been knocked out [27]. The knockout constructs of Ngly1 and Engase are shown in Fig 1B and 1C, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this ERAD dysregulation could be reversed in cells by an additional ENGASE gene knockout. 4 Furthermore, the most recent mouse model showed that the ENGASE gene deletion could partially rescue the lethality of Ngly1-deficient mice and mitigate the phenotypes. 5 Therefore, ENGase is proposed as a promising drug target for treating human NGLY1 deficiency (Scheme 1).…”
mentioning
confidence: 99%